Economic evaluation of environmental management programmes - Murty, M. N. (New Delhi, 1988)
Conservation of environmental resources is very important without which nature's balance will be dis turbed which, in turn, may make life on the globe more miserable. Pre servation involves incremental cost to the society with probably more than compensating incremental benefits. This book provides a succinct review of various methods of evaluation of economic effects of management of environmental resources. It also discusses at length issues relating to the relative efficacy of alternative pro grammes for the environmental pollu tion abatement. As an illustration of the practicability of methodological issues discussed, it presents a detailed case study of the economic evaluation of water pollution abatement.
Keywords: Environmental policy